Mobile stories: the evolution of a mobile, collaborative story reading and creation tool for children. (3rd April 2012) - Fails, Jerry Alan; Druin, Allison; Guha, Mona Leigh
This paper discusses design iterations of mobile stories – a mobile technology that empowers children to collaboratively read and create stories. We present the design and discuss the impact of different collocated collaborative configurations for mobile devices including content splitting and space sharing . We share design experiences that illustrate how mobile stories support collaboration and mobility, and identify how the collocated collaborative configurations are best suited for reading and sharing tasks. We also identify how creative tasks foster more mobility and dynamic interactions between collaborators.